Analysis of Passenger Satisfaction Level of Departure Terminal Facilities at Sam Ratulangi International Airport Manado - Muzna Inna Din; Ristiani Ristiani (CV. Rayyan Dwi Bharata, 2023)
The purpose of this research is to find out how the existing facilities are at Sam Ratulangi Manado International Airport Departure Terminal, to find out how the level of passenger satisfaction with the existing facilities at the Departure terminal at Sam Ratulangi International Airport Manado. The research method used in this study is a qualitative method and the type of research used is a case study and a quantitative method. The types of data used in this study are primary data including survey results using the CSI method regarding the level of satisfaction of passengers with departure terminal facilities, observation results and documentation results, and secondary data including articles, Decree of the Director General No. 77 of 2005, and documentation. The research is located at Sam Ratulangi International Airport Manado. The data analysis technique used includes the validity of qualitative data which consists of a credibility test, transferability test, dependability test, and confirmability test. Quantitative data validity test consisting of validity test and reliability test. And the data analysis used includes: data collection, data reduction, data presentation, conclusion drawing, and the Customer Satisfaction Index (CSI) method. From the results of the data conducted by researchers, this study resulted that the existing conditions of the departure terminal facilities at Sam Ratulangi Manado International Airport were fairly complete and had met service standards in accordance with Directorate General Decree No. 77 of 2005 concerning Technical Requirements for the Operation of Airport Engineering Facilities, it can be seen from the results of the data obtained and the results of observations that were examined by the researchers as well as the survey results obtained by the researchers that the level of passenger satisfaction with the Sam Ratulangi Airport Departure Terminal facilities in Manado.